Diferenciación poblacional en la talla corporal de la liebre de Tehuantepec (lepus flavigularis) - Rico, Yessica; Lorenzo, Consuelo; López, Sergio (Instituto de Ecología, A.C., 2008)
In this work we analyzed the body size differentiation of three populations of the Tehuantepec jackrabbit, Lepus flavigularis, in the Isthmus of Tehuantepec, Oaxaca, Mexico. Linear regression analysis between body size and body weight were statistically significant for the males and females from the population of Santa María del Mar, and for the males from Montecillo Santa Cruz, but not for the females. In addition, the regression analysis for the males of Aguachil was not significant. The ANOVAanalysis revealed that jackrabbits from Santa María del Mar were statistically significant larger than the jackrabbits from Aguachil and Montecillo Santa Cruz. The results were coincident with the genetic data that highlight the genetic differentiation of Santa María del Mar of the rest of populations. It is possible that the differences in body size are related with the ecological characteristics of the habitat prevailing in each population of jackrabbits.